Attention disorders in patients with depression in wartime conditions - Отрощенко, Наталія; Kupchynskyi, Roman (Psychosomatic Medicine and General Practice, 2025)
Introduction. The significant increase in the prevalence of depression worldwide, particularly in Ukraine among victims of Russian aggression, as well as the importance but insufficient development of psychological and psychiatric care for patients with psychogenic depression with attention disorders in wartime conditions determine the relevance of this study. These disorders significantly impair patients' quality of life, complicate daily functioning, professional activity, and the ability to cope with the stresses of war, and also create a risk of suicidal behavior. Despite the current level of achievement in psychiatry and psychology, there is an urgent need to improve methods of early diagnosis and develop targeted treatment and rehabilitation programs aimed at overcoming these disorders. Objective. To identify ways to improve psychological and psychiatric care for patients with depression and attention disorders in wartime conditions by conducting an analytical study of national and foreign literature on these issues. Materials and methods. A review of the literature on depression with attention disorders, mainly from the last 5 years, was conducted in the international databases PubMed, Google Scholar, Web of Science, and Scopus using methods of systematization, analysis, and generalization by keywords. Conclusions. The study confirms the significant prevalence of depression with attention disorders among victims of the war in Ukraine, the insufficient development of clinical and psychological aspects, and the need for further study of this problem, as well as the creation of state measures for psychological and psychiatric assistance for these patients. Keywords: depression, attention disorder, wartime conditions, diagnostics, treatmentpsychological and psychiatric care